Thermal Stimuli‐Triggered Drug Release from a Biocompatible Porous Metal–Organic Framework. Issue 42 (6th July 2017) - Jiang, Ke; Zhang, Ling; Hu, Quan; Zhang, Qi; Lin, Wenxin; Cui, Yuanjing; Yang, Yu; Qian, Guodong
Abstract: Drug delivery carriers with a high drug loading capacity and biocompatibility, especially for controlled drug release, are urgently needed due to the side effects and frequently dose in the traditional therapeutic method. In our work, a Zr‐based metal–organic framework named ZJU‐801, which is isoreticular with NU‐801, has been designed and further demonstrated as an excellent drug delivery system (DDS) with a high drug loading of 41.7 %. Such a high drug loading capacity may be ascribed to the appropriate match of the size and the large pore volume of this kind of Zr MOF material. Compared with DS@NU‐801, this DDS has successfully achieved on‐command heating‐activated drug release, which was probably attributed to the bulkier ligand, the better stability, and the intense π–π interaction between ZJU‐801 and diclofenac sodium (DS) demonstrated comprehensively by SEM, powder X‐ray diffraction (PXRD), FTIR and 13 C solid‐state NMR spectroscopy as well as computer simulations. It is worth noting that premature drug release was avoided effectively without any complicated post‐modifications. The low cytotoxicity and good biocompatibility of our DDS were certificated by the in vitro favorable results from an MTT assay, a WST‐1 assay, and confocal microscopy imaging. Abstract : The heat is on : The isoreticular Zr‐cluster‐based metal–organic framework (MOF) ZJU‐801 was synthesized with high drug loading capacity for thermal stimuli‐triggered drug release (see figure, DS=diclofenac sodium), thus it could be used as a local heating method for treatment of disease including cancer.